Developing Students’ Ability to Master English Idioms using Songs and Pictures - Dian Candra Prasetyanti; Riana Eka Budiastuti; Siti Aimah (Universitas Muhammadiyah Semarang, 2017)
Learning English idioms is difficult not only for native speakers but also for ESL/EFL learners because they donot mean what they literary mean and the meaning of idioms is difficult to understand except they make use oftheir cultural understanding. Learning English idioms is a challenging task for Indonesian students who learnEnglish as a Foreign Language (EFL).The objective of this study was to investigate the effect of songs andpicturesto teach English Idiomsof University students at University of Muhammadiyah Semarang. To conductthe study, 15 students from the second semester class of English Education Department were choose. Therefore,this research presents the effective learning strategies for EFL learners in Indonesia to learn English idiomseffectively. Besides introducing English idioms to the University students using songs and pictures it can be theway to increasing students’ motivat ion and involvement in learning English idioms. Keywords: English idioms, songs, pictures.